2020
DOI: 10.1007/s42452-020-03940-3
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the effects of deep cryogenic treated WC–Co insert on turning of Al6063 using multi-objective optimization

Abstract: To improve the machining performance manufacturers adopt various methods to improve the tool life which influences production cost and the degree of the surface finish. Recently cryogenic treatment is used to improve the machining performances. In the present work, the tungsten carbide-cobalt (WC-Co) cutting tool is cryogenically treated at − 196 °C for a soaking time of 24 h and tempered to 200 °C for 2 h. The machinability attributes such as Tool Wear Rate, Surface profile roughness (Ra), of the Cryo Treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Additionally, the microhardness of the WC-Co alloy also increases by approximately 5.7%. 20,29 In this work, cryoprocessing of the alloy for 16-24 h increased the material's mechanical properties (hardness and elasticity). It was also shown that waterjet treatment has a more negligible effect on the properties of the alloy after exposure to −192 °C for 24 h. In Fomin, 9 the titanium composite was processed thermally.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Additionally, the microhardness of the WC-Co alloy also increases by approximately 5.7%. 20,29 In this work, cryoprocessing of the alloy for 16-24 h increased the material's mechanical properties (hardness and elasticity). It was also shown that waterjet treatment has a more negligible effect on the properties of the alloy after exposure to −192 °C for 24 h. In Fomin, 9 the titanium composite was processed thermally.…”
Section: Discussionmentioning
confidence: 70%
“…15 Solid materials are also used to create cutting, grinding, milling, or other tools for their processing. 9,17 The main methods of superhard material treatment include shot blasting, vibration hardening, 11 pulsed plasma processing, 18 laser processing, 19 heat treatment, 20 and others. All of them enhance the strength characteristics of finished structures, thus reducing fatigue failure.…”
mentioning
confidence: 99%
“…Various researchers have attempted to determine the effectiveness of the parameters affecting turning operations on CNC lathes. A surface roughness of 0.36 µmRa was obtained by the automatic turning of Al6063 alloy on CNC lathes using Takushi analysis [1] and the machining of aluminum alloy grades 6063 with tungsten carbide (WC+Co) insert by deep cryogenic treatment gives a surface roughness of 0.373 µmRa with optimal parameters [2]. They demonstrated the effectiveness of the parameters in turning Al6063.…”
Section: Introductionmentioning
confidence: 92%
“…2. This study was performed consisted of 3 main processes: the first is a rough turning process to remove the outer of the workpiece approximately -0.5 mm, the second is finished turning, in which the parameters have been studied in the previously achieved machining of aluminum alloy within 0.373 µmRa which can be applied in this finish turning of Al6063 [1][2]. The turning parameters are a spindle speed of 2500 RPM, feed rate of 0.5 mm/rev and depth of cut of 100 µm with cutting tool insert MITSUBISHI code TNMG160402L-2G NX2525.…”
Section: The Single Roller Burnishing Toolsmentioning
confidence: 99%
“…It is observed that DCT insert exhibits the better surface profile finish while machining of AISI 4340 steel compared to UT insert. Arunkarthikeyan et al [34][35][36][37] reported that cryo treated carbide tools will provide improved surface characteristics even at high-speed machining.…”
Section: Surface Profile Roughness Analysismentioning
confidence: 99%